2008
DOI: 10.1097/01.ccm.0000295425.41831.85
|View full text |Cite
|
Sign up to set email alerts
|

Modification of acute cardiovascular homeostatic responses to hemorrhage following mild to moderate traumatic brain injury

Abstract: Acute mild and moderate traumatic brain injury disrupts cardiovascular homeostatic responses to extracranial hemorrhage; this disruption is graded according to the severity of traumatic brain injury. Severe disruption is associated with an increase in early mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 39 publications
2
11
0
1
Order By: Relevance
“…26,27 McMahon et al, also found a similar association between brain-specific injury and cardiovascular response to hemorrhage in rats where heart rate remained elevated longer and there was a delayed hypotensive response to graded fixed-volume hemorrhage with TBI. 28 However, other investigators have found impaired vascular responses similar to our witnessed response during hemorrhage and resuscitation in a rat model where vascular compensation was blunted in the setting of TBI. 29 Our data agrees with an immediate attenuation of initial tachycardia and impaired peripheral vasoactivity during hemorrhage and fluid resuscitation in the setting of brain injury.…”
Section: Discussionsupporting
confidence: 65%
“…26,27 McMahon et al, also found a similar association between brain-specific injury and cardiovascular response to hemorrhage in rats where heart rate remained elevated longer and there was a delayed hypotensive response to graded fixed-volume hemorrhage with TBI. 28 However, other investigators have found impaired vascular responses similar to our witnessed response during hemorrhage and resuscitation in a rat model where vascular compensation was blunted in the setting of TBI. 29 Our data agrees with an immediate attenuation of initial tachycardia and impaired peripheral vasoactivity during hemorrhage and fluid resuscitation in the setting of brain injury.…”
Section: Discussionsupporting
confidence: 65%
“…Previous work with rodent TBI models collectively supports the premise that TBI causes loss of hemodynamic resilience (i.e., the ability to regulate vascular tone during hemorrhagic shock), and in so doing alters the resuscitative needs (Yuan et al, 1991;Yuan and Wade, 1992;Law et al, 1996;McMahon et al, 2008). Airblast also acutely disrupted cardiovascular compensatory responses to hemorrhage; we observed a significant reduction in PSBV and time to PSBV (i.e., cardiovascular decompensation), as well as the survival time with sustained reduction in MAP (Fig.…”
Section: Blast Overpressure In Ratsmentioning
confidence: 86%
“…Fluid percussion injury data from several laboratories indicate that TBI adversely affects cardiovascular homeostatic responses to blood loss and resuscitation (Yuan et al, 1991;Yuan and Wade, 1992;Law et al, 1996;McMahon et al, 2008). It is very likely that the blast-induced brain trauma also substantially alters fluid resuscitation requirements, particularly when one considers that it occurs in combination with deleterious effects on other organ systems.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several studies have shown that TBI may impair cardiovascular compensation to acute blood loss [12-16]. In detail, it has been demonstrated that the autonomic response to haemorrhage is disturbed in the presence of TBI and the physiological response to acute blood loss, like hypotension or the modification of vascular tone may be impaired or delayed [14,15,17]. Yuan and colleagues even demonstrated that TBI may suppress spontaneous hemodynamic recovery from hemorrhage and also impede the efficacy of fluid resuscitation [12,18].…”
Section: Introductionmentioning
confidence: 99%